A study on the concept of online business from the Islamic perspective / Nur Affza Abd Malek - Abd Malek, Nur Affza (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2017)
As we know, there are many Quranic verse and Hadith regarding business in Islam however, none explains about online business. But, Muslim scholars have studied about it and elaborate about online business in Islamic perspective. In fact, online business is spreading around the world but most of it does not practice muamalah rulings because either they have no knowledge about it or they do not want to practice muamalah rulings in their online business. Another problem of Islamic online business is lack of study about it because people more focus to study on Islamic banking rather than Islamic online business. So, this study aims to study the background of online business according to Islamic perspective and explain the muamalah rulings needed in an online transaction. Moreover, this study is to know the understanding of online users which are the online sellers and online buyers about Islamic online business. Online business in Islamic perspective is business transaction that happens between the contracting parties through computer and has Shariah guidelines to be followed to ensure the transaction happens in online business is valid and the validity of Islamic online business consists of offer and acceptance, contracting parties (online sellers and buyers) and also the subject matter so if any of the condition is not fulfilled, the transaction consider invalid and null. Besides, there are few respondents were asked through interview session about Islamic online business and other information to know more about their understanding and participation in online business. Hence, this study explains about the online business according to Islamic perspective, the differences between Islamic and conventional online business, the benefits and reasons on participating in Islamic online business and also problems arising from Islamic online business. In this study, it can be concluded that the objectives have been achieved successfully based on the elaboration of the findings of this research.